Pelatihan Keterampilan Guru dalam Membuat Perencanaan Pembelajaran Sains Anak Usia Dini - Ernawulan Syaodih; Leli Kurniawati; Hany Handayani; Dadan Setiawan; Indra Suhendra (Universitas Mathla'ul Anwar Banten, 2020)
TEACHER’S SKILL TRAINING IN DESIGNING SCIENCE LEARNING IN EARLY CHILDHOOD. One of the competencies that must be possessed by an Early Childhood Education (PAUD) teacher is the competency to design and implement the learning process. Based on field studies, PAUD teachers have difficulty in designing and implementing science learning in early childhood. Science is considered a complicated subject and is difficult to learn especially for young children. The material that is difficult to understand and teach is what makes PAUD teachers lazy and ignores science learning, even though science learning can be taught through a variety of fun and exciting activities in accordance with PAUD learning objectives namely Play while learning. Through a variety of play activities children can learn science with fun and fun in accordance with the level of early childhood development. Teaching ability is one of the competencies that PAUD teachers must possess in developing professionalism. Continuing professional development must be based on the needs of the teacher concerned. The need in question is the need to achieve and improve competence above the teacher professional competency standard. This will also at the same time have implications for the acquisition of credit numbers for promotion or functional positions of teachers. The purpose of this activity is to improve the ability of early childhood education teachers in designing and implementing science learning. Participants in this activity numbered 100 PAUD teachers in Bandung Regency. The results of this activity show that PAUD teachers are able to design and implement science experiment activities for young children after training.